hsCRP levels as predictor of difficult laparoscopic cholecystectomy- current status evaluation experience in a teaching institution - Arora, Balvinder Singh; Sen, Poornima; Singh, Raj Kumar; Biswal, Indu; Paruthy, Shivani B. (International Surgery Journal, 2017)
Background: CRP, an acute phase reactant, is known to increase up to 1000 folds following inflammation and/or infection, but it’s utility as a significant predictor of difficult LC or need for conversion to OC still remains controversial. Limited studies on levels of hsCRP and its association with difficult cholecystectomy are available in literature, especially in Indian context. It is hypothesized that levels of hsCRP pre-operatively for a given population or an individual patient if high would help a surgeon anticipate better a difficult LC, avoid excessive intra-operative manipulations, go for conversion early, reduce time of surgery and hence also minimise post-operative complications. Methods: The present included 30 clinically diagnosed ‘cholecystitis with cholelithiasis’ patients, and 30 healthy individuals. For accurate comparison of hsCRP levels, a fasting and post-operative, 6 and 12 hours, blood samples were analyzed by ELISA test. Pre-and post-operative hsCRP values were recorded and analyzed using multi-user licensed SPSS- Version 21.0. Results: The mean value of hsCRP in controls was 1.43mg/L. In study group, in pre-operative serum samples, the concentration was 20.46 mg/l. At 6 and 12 hours post-operative periods, the mean values observed were 24.4mg/L and 23.7 mg/L respectively. Compared with controls, the mean values are fairly high and statistically also significant (p-values <0.0001). For the study group comparison of hsCRP value pre-operative and post-operatively 6 hours, using Wilcoxon Signed Rank Test has given the p-value <0.001 indicating that the increased hsCRP concentration in patients’ circulation is highly significant as a predictor of difficult laparoscopic cholecystectomy. Similarly, Comparison of hsCRP value pre-operative and post-operative 12 hours, using Wilcoxon Signed Rank Test revealed the p-value <0.007 showing it as highly significant and a predictor of difficult LC requiring conversion. The preoperative value of 20.46% is significant for an individual planned for LC who may require conversion. Conclusions: The preoperative hsCRP value of 20.64mg/L, as per our study results, can be relied upon as predictors of difficult LC and/or need for conversion not only in the study group in the given population but also in individual cases. Such a value of 20.64mg/L is definitely important for an individual case management. Knowing the preoperative values beforehand and if found high, it places a surgeon on a cautious note to avoid too much of LC manipulations intra-operatively, take an early decision to go for conversion, reduce the time of surgery, minimise post-operative complications and hence also morbidity.